Historical Demography in Hungary: a history of research - Tamaś Farago\' (Hungarian Demographic Research Institute, 2013)
In sketching an outline of historical demography in Hungary, two successive periods can and must be considered in relation to two territories. One of these lasts from the Middle Ages to the end of the First World War; this is the historical Kingdom of Hungary, namely the whole area of the Carpathian Basin, and the greater part of today's Croatia. This territorial approach has two advantages and two minor disadvantages. Its most important advantage is that it seems to be congruent with the geographical area in which the relevant social and demographic processes took place from the Middle Ages to the early twentieth century, and to which the integrated sources refer. In addition, demographic research within this framework (and this is the second advantage) makes the region a kind of laboratory of demographic analysis, since it offers a wider range of comparisons compared to other European countries owing to the great cultural, economic and geographical variety of the Carpathian Basin. Related to this are disadvantages, though these are far less important from a professional point of view. These arise from the fact that nowadays sources are spread across archives held in seven different countries, and from the fact that scientific publications and documents written over the last 80 to 90 years are written in several different languages; indeed, Latin, German and Hungarian, which were necessary for understanding earlier sources, may no longer be sufficient. The second territory and period to be investigated by historical demography in Hungary is the one that has existed from 1920 to the present day. Demographic processes since then have (to much of an extent) taken place within this territory, and sources suitable for the reconstitution of these are also created following the administrative structure of this area. From what has been said so far, it can be clearly inferred that a basic question for Hungarian historical demographic research is the chronological framework used for its analysis. The development of the population in Hungary can be divided into three basic periods. The first division line is demarcated by the acceleration of the disintegration of the traditional demographic system and the beginning of the demographic transition which took place around the 1870s.2 Naturally, these division lines are flexible. In the economically and socially underdeveloped peripheries – especially in the mountainous regions of the Carpathians – and in the social groups abandoning their old social and demographic patterns more slowly (for example gypsy communities) this turning point slips to a later date.
Keywords: B24; 300; Intergenerationale Übertragung; Hausarbeit; Zeitverwendung; Generationengerechtigkeit; Öffentliche Sozialleistungen; Lebensverlauf; Ungarn